Natural Particulate Reinforced Biocomposite Film: A Review - S. Rathinavel; S. S. Saravanakumar; T. S. Senthilkumar; P. Senthamaraikannan; Indran Suyambulingam; R. Kumar (Journal of Natural Fibers)
Biocomposite films, which incorporate natural waste materials as fillers and biodegradable polymers as matrix material, have gained significant attention as sustainable alternatives to traditional plastic-based materials. This article aims to give potential insights into the role of natural waste particulates in improving biopolymer-based biocomposite film properties and reducing the use of traditional plastic-based materials in different applications. This review article is structured to explore the different natural waste materials utilized along with different biopolymers to prepare biocomposite films. It also highlights the influence of natural filler on the thermal, mechanical, antibacterial, and barrier properties of biopolymer-based biocomposite films. Significant improvements in tensile strength, tensile modulus, thermal stability, and antibacterial and barrier properties were reported due to the synergy between natural waste materials and biopolymers, making them suitable for packaging, biomedical, and optoelectronics applications. This literature review provides a gap in the understanding of the importance of natural particulates in developing new biocomposite films for possible applications in many areas.